Reversed Phase HPLC-DAD Profiling of Carotenoids, Chlorophylls and Phenolic Compounds in Adiantum capillus-veneris Leaves - Zeb, Alam; Ullah, Fareed (Frontiers in Chemistry, 2017)
Adiantum capillus-veneris is important endangered fern species with several medicinal properties. In this study, the leaves samples were extracted and separated using reversed phase HPLC with DAD for carotenoids, chlorophylls and phenolic compounds. Separation of carotenoids and chlorophylls were carried out using a tertiary gradient system of water, MTBE and methanol-water, while a binary gradient system of methanol-water-acetic acid was used for phenolic profiling. Results revealed eight carotenoids, four pheophytins and two chlorophylls. Lutein (806.0 µg/g), chlorophyll b′ (410.0 µg/g), chlorophyll a (162.4 µg/g), 9'-Z-neoxanthin (142.8 µg/g) and all-E-violaxanthin (82.2 µg/g)) were present in higher amounts. The relatively high amounts of lutein may be one of the key indicator of beneficial antioxidant properties. The phenolic profile revealed a total of thirteen compounds, namely p-hydroxybenzoic acid, chlorogenic acid, caftaric acid, kaempferol glycosides, p-coumaric acid, rosmarinic acid, 5-caffeoylquinic acid, and quercetin glycosides. Kaempferol-3-sophorotrioside (58.7 mg/g), chlorogenic acid (28.5 mg/g), 5-O-caffeoylquinic acid (18.7 mg/g), coumaric acid (11.2 mg/g) and its derivative (33.1 mg/g) were present in high amounts. These results suggest that the reversed phase HPLC profiling of adiantum leaves provides a better understanding in to the actual composition of bioactive compounds, which may be responsible for possible medicinal properties. Adiantum leaves rich in important bioactive phytochemicals can be used as a potential source of nutraceuticals or as a functional food ingredient.